Macrocycles : construction, chemistry, and nanotechnology applications - Davis, Frank, 1966-; Higson, Seamus (Hoboken : Wiley, 2011)
'Advanced undergraduate and postgraduate students of organic, inorganic and analytical chemistry, materials science and nanotechnology'--
Machine generated contents note: Preface. -- 1. Introduction. -- 1.1. Simple ring compounds. -- 1.2. Three dimensional aliphatic carbon structures. -- 1.3. Annulenes. -- 1.4. Multi-ring aromatic structures. -- 1.5. Porpyrins and phthalocanines. -- 1.6. Conclusions. -- References. -- 2. Cyclophanes. -- 2.1. Introduction to cyclophanes. -- 2.2. Cyclophanes with one aromatic system and aliphatic chain. -- 2.3. Cyclophanes with more than 1 aromatic ring. -- 2.4. Napthalenophanes and other aromatic systems. -- 2.5. Cyclophanes containing heteroaromatic systems. -- 2.6. Ferrocenophanes. -- References. -- 3. Crown ethers, cryptands and other compounds. -- 3.1. Introduction. -- 3.2. Crown ethers. -- 3.3. Simple complexes with crown ethers. -- 3.4. Azacrowns, cyclens and cyclams. -- 3.5. Crowns containing other heteroatoms. -- 3.6. Lariat and bibracchial crown ethers. -- 3.7. Cryptands. -- 3.8. Spherands. -- 3.9. Combined and multiple systems. -- 3.10. Applications of crown ethers and related compounds. -- 3.11. Conclusions. -- References. -- 4. Calixarenes. -- 4.1. Introduction to calixarenes. -- 4.2. History of the calixarenes. -- 4.3. Structures of calixarenes. -- 4.4. Chemical modification of calixarenes. -- 4.5. Complexes with calixarenes. -- 4.6. Bis- and multicalixarenes. -- 4.7. Oxacalixarenes, azacalixarenes and thiacalixarenes. -- 4.8. Resorcinarenes - synthesis and structure. -- 4.9. Cavitands and carcerands. -- 4.10. Uses of calixarenes and conclusions. -- References. -- 5. Heterocalixarenes and calixnaphthalenes. -- 5.1. Introduction to heterocalixarenes and calixnaphthalenes. -- 5.2. Calixnaphthalenes. -- 5.3. Tropolone based macrocycles. -- 5.4. Calixfurans. -- 5.5. Calixpyrroles. -- 5.6. Calixindoles, calixpyridines and calixthiophenes. -- 5.7. Conclusions. -- References. -- 6. Cyclodextrins. -- 6.1. Introduction to cyclodextrins. -- 6.2. Complex formation by cyclodextrins. -- 6.3. Cyclodextrins of other sizes. -- 6.4. Modification reactions of cyclodextrins. -- 6.5. Selectivity of cyclodextrins. -- 6.6. Multiple cyclodextrin systems. -- 6.7. Polymeric cyclodextrins. -- 6.8. Cyclodextrins combined with other macrocyclic systems. -- 6.9. Therapeutic uses of cyclodextrins. -- 6.10. Other uses of cyclodextrins. -- 6.11. Conclusions. -- References. -- 7. Cyclotriveratylenes and cryptophanes. -- 7.1. Introduction to cyclotriveratrylenes and cryptophanes. -- 7.2. Synthesis of cyclotriveratrylenes. -- 7.3. Modification of cyclotriveratrylenes. -- 7.4. Synthesis of optically active cyclotriveratrylenes. -- 7.5. Modification of the bridging groups. -- 7.6. Modification of the aromatic rings with organometallic groups. -- 7.7. Selective binding applications of cyclotriveratrylenes. -- 7.8. Analogues of CTV. -- 7.9. Cryptophanes - synthesis and structure. -- 7.10. Cryptophanes - chemical modification. -- 7.11. Complexes with cryptophanes. -- 7.12. Cryptophane/Xenon complexes. -- 7.13. Other uses of cryptophanes. -- 7.14. Hemicryptophanes. -- 7.15. Conclusions. -- References. -- 8. Cucurbiturils. -- 8.1. Introduction to cucurbiturils. -- 8.2. Complexation behaviour of simple cucurbiturils. -- 8.3. Modification of cucurbiturils. -- 8.4. Uses of cucurbiturils. -- 8.5. Hemicucurbiturils. -- 8.6. Conclusions. -- References. -- 9. Rotaxanes and catenanes. -- 9.1. Introduction to rotaxanes and catenanes. -- 9.2. Rotaxanes. -- 9.3. Rotaxanes as molecular machines. -- 9.4. Thin films of rotaxanes. -- 9.5. Polyrotaxanes. -- 9.6. Catenanes. -- 9.7. Switchable catenanes. -- 9.8. Catenanes on surfaces. -- 9.9. Polycatenanes and catenated polymers. -- 9.10. Natural catenanes. -- 9.11. Conclusions. -- References. -- 10. Other supermolecular systems, molecular motors, machines and nanotechnological applications. -- 10.1. Introduction. -- 10.2. Other molecular systems. -- 10.3. Molecular devices, motors and machines. -- 10.4. Conclusions. -- References.
Includes bibliographical references and index.
Keywords: Macrocyclic compounds; TECHNOLOGY & ENGINEERING / Material Science